2020
DOI: 10.19173/irrodl.v21i4.4643
|View full text |Cite
|
Sign up to set email alerts
|

Recommender Systems for MOOCs: A Systematic Literature Survey (January 1, 2012 – July 12, 2019)

Abstract: In recent years, massive open online courses (MOOCs) have gained popularity with learners and providers, and thus MOOC providers have started to further enhance the use of MOOCs through recommender systems. This paper is a systematic literature review on the use of recommender systems for MOOCs, examining works published between January 1, 2012 and July 12, 2019 and, to the best of our knowledge, it is the first of its kind. We used Google Scholar, five academic databases (IEEE, ACM, Springer, ScienceDirect, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 98 publications
0
29
0
Order By: Relevance
“…However, there are several challenges and opportunities in implementing those techniques in the context of course RS as we described in Section 1. Although there are several systematic review papers [116][117][118] published on specific learning platforms such as; MOOCs (Massive Open Online Courses) and e-Learning RS, still lacks systematic literature reviews for course RS in general [119]. Hence, primary focus of this research is to investigate current and emerging approaches applied in course RS in the recent research literature and also to outline the avenues for the future research.…”
Section: Systematic Review Processmentioning
confidence: 99%
“…However, there are several challenges and opportunities in implementing those techniques in the context of course RS as we described in Section 1. Although there are several systematic review papers [116][117][118] published on specific learning platforms such as; MOOCs (Massive Open Online Courses) and e-Learning RS, still lacks systematic literature reviews for course RS in general [119]. Hence, primary focus of this research is to investigate current and emerging approaches applied in course RS in the recent research literature and also to outline the avenues for the future research.…”
Section: Systematic Review Processmentioning
confidence: 99%
“…This study also reported that the dominant perspective published by public media was about the role of MOOC in revolutionizing higher education, which was likely to boost the public's acceptance of the changes in existing higher education structures. focused on how technology and artificial intelligence can be used to improve teaching and learning in MOOCs was also documented (Adham et al, 2016;Khalid et al, 2020;Lundqvist et al, 2020).…”
Section: Research On Moocs In New Zealandmentioning
confidence: 99%
“…With the continuous development of big data technology, MOOC resource recommendation algorithms have emerged. With the help of recommendation technologies in the fields of e-commerce, tourism routes, and social networks, many excellent MOOC resource recommendation algorithms have been proposed [6,7]. Traditional courses only have dozens or hundreds of students, but a MOOC can hold more than 100,000 people at most.…”
Section: Introductionmentioning
confidence: 99%